Extremely high aerosol loading over Arabian Sea during June 2008: The specific role of the atmospheric dynamics and Sistan dust storms - Kaskaoutis, D. G.; Rashki, A.; Houssos, E. E.; Goto, D.; Nastos, P. T. (Atmospheric Environment, 2014)
This study focuses on analyzing the extreme aerosol loading and the mechanisms, source areas and meteorological conditions that favored the abnormal dust exposure towards Arabian Sea during June 2008. The analysis reveals that the spatial-averaged aerosol optical depth (AOD) over Arabian Sea in June 2008 is 0.5 (78.2%) higher than the 2000-2013 mean June value and is mostly attributed to the enhanced dust activity and several (18) dust storms originated from the Sistan region (Iran-Afghanistan borders). Landsat images show that the marshy lakes in Sistan basin got dried during the second half of June 2008 and the alluvial silt and saline material got easily eroded by the intense Levar winds, which were stronger (>15-20ms-1) than the climatological mean for the month of June. These conditions led to enhanced dust exposure from Sistan that strongly affected the northern and central parts of the Arabian Sea, as forward air-mass trajectories show. The NCEP/NCAR reanalysis reveals an abnormal intensification and spatial expansion of the Indian low pressure system towards northern Arabian Sea in June 2008. This suggests strengthening of the convection over the arid southwest Asia and exposure of significant amount of dust, which can reach further south over Arabian Sea favored by the enhanced cyclonic circulation. MODIS imagery highlighted several dust storms originated from Sistan and affecting Arabian Sea during June 2008, while the SPRINTARS model simulations of increased AOD and dust concentration over Sistan and downwind areas are in agreement with ground-based and satellite observations. © 2014 Elsevier Ltd.
Keywords: aerosol; air mass; Arabian Sea; article; Asia; Atmospheric aerosols; computer simulation; controlled study; Dust control; dust exposure; dust storm; Dust storms; Indian Ocean; land use; Landsat; Loading; marine environment; Meteorology; mineral dust; MODIS; optical depth; Particulate emissions; priority journal; radiative forcing; remote sensing; Satellite imagery; sea; sea surface temperature; seashore; seasonal population dynamics; seasonal variation; Severe AOD; simulation; SPRINTARS; Storms; Synoptic meteorology; Weather; wind